Open and laparoscopic resection of hepatocellular adenoma: trends over 23 years at a specialist hepatobiliary unit. Issue 9 (23rd May 2014) - de'Angelis, Nicola; Memeo, Riccardo; Calderaro, Julien; Felli, Emanuele; Salloum, Chady; Compagnon, Philippe; Luciani, Alain; Laurent, Alexis; Cherqui, Daniel; Azoulay, Daniel
Abstract Background Hepatocellular adenoma (HCA) is a rare benign liver epithelial tumour that can require surgery. This retrospective study reports a 23‐year experience of open and laparoscopic resections for HCA. Methods Patients with a histological diagnosis of HCA were included in this analysis. Surgical resection was performed in all symptomatic patients and in those with lesions measuring > 5 cm. Results Between 1989 and 2012, 62 patients, 59 of whom were female, underwent surgery for HCA (26 by open surgery and 36 by laparoscopic surgery). Overall, 96.6% of female patients had a history of contraceptive use; 54.8% of patients presented with abdominal pain and 11.2% with haemorrhage; the remaining patients were asymptomatic. Patients who underwent laparoscopy had smaller lesions (mean ± standard deviation diameter: 68.3 ± 35.2 mm versus 91.9 ± 42.5 mm; P = 0.022). Operatively, laparoscopic and open liver resection did not differ except in the number of pedicle clamps, which was significantly lower in the laparoscopic group (27.8% versus 57.7% of patients; P = 0.008). Postoperative variables did not differ between the groups. Mortality was nil. Two surgical specimens were classified as HCA/borderline hepatocellular carcinoma. At the 3‐year follow‐up, all patients were alive with no recurrence of HCA. Conclusions Open and laparoscopic liver resections are both safe and feasible approaches for the surgical management of HCA. However, laparoscopic liver resections may be limited by lesion size and location and require advanced surgical skills.